Bridging the Epistemic Gap: Reconstructing the Regulation of Scientific Evidence in Indonesia’s Anti Corruption Judiciary - Fransiscus Nanga Roka; Yovita Arie Mangesti (DiH: Jurnal Ilmu Hukum, 2026)
This research concerns about the epistemic cleavage of legal doctrine and scientific methodology in Indonesia’s anti-corruption judiciary through discussing non-existence formal concept of scientific evidence. The study seeks to provide a re-construction of the concept of legal recognition with respect to scientific evidence as an independent category in Indonesian procedural law so that there could be certainity and justice. Applying a normative juridical approach with statutory, conceptual and comparative studies, this article examines existing regulations between KUHAP and anti-corruption law as well as compared to other legal systems which considered foreign models of the United States, the United Kingdom, Germany or others. The verdicts also expose a gap and a lack of uniformity in terms of the admissibility and assessment of forensic as well as digital evidence in cases related to corruption, creating confusion and eroding judicial authority. The originality of this study is to offer multidimensional reconstruction paradigm, combining with epistemic reliability, chain of custody standards, and judges′ gatekeeping responsibilities, enlightened by other jurisdictions but retains civil law tradition in Indonesia. The proposed forensic model focuses on method validation, ISO-oriented certification and judicial education to enhance evidence assessment. That reconstruction should be expected to improve the transparency of the judiciary, foster forensic accountability, and bring Indonesia in line with international best practices on corruption.